Inflation Differences in the Russian Regions: an Empirical Analysis - Sinelnikov-Murylev, Sergey Germanovich; Perevyshin, Yury Nikolaevich; Trunin, Pavel Vyacheslavovich (Economy of Regions, 2020)
The article addresses the difference between regional inflation rates, and criteria that determine such variations. Moreover, it examines whether inflation differences in the Russian regions significantly affect a unified monetary policy targetting a 4 per cent inflation. Using panel econometric methods with instrumental variables, we identified the factors creating regional inflation difference: a) output gap, b) inflation expectations, c) exchange rate pass-through, d) and regional price convergence. Then, we explained how these factors influence regional inflation, using the modern theoretical models that are based on the neo- Keynesian logic. Additionally, we discussed the problems caused by regional inflation differences. Since the convergence of price levels to the average Russian level is the key factor influencing regional inflation differences, such differences do not constitute a problem for the unified monetary policy aimed at a 4 % inflation target. In the study, we have determined the causes of inflation differences in the Russian regions, the majority of which result from the new Keynesian Phillips curve. The obtained results can be applied for developing regional economic policies aimed at synchronizing inflation in the Russian regions, as well as for modelling the consequences of monetary policy for regional economies.